Dynamique d’occupation du sol des zones humides urbanisées de Dakar (Sénégal) de 1942 à 2014 - Diop Aimée; Hyacinthe Sambou; Cheikh Diop; Elysée Ntiranyibagira; Honoré Dacosta; Bienvenu Sambou (VertigO)
The study is an analysis of the land cover spatial dynamics of the wetlands (Niayes) of Dakar from 1942 to 2014 by the use of geomatic tools. We used the aerial photographs of the years 1942, 1966 and 1978 and the satellite images of the years 2003 and 2014 to establish land-cover maps. The results of the analysis show that the big drought of the 1970s affected the hydrology of the Niayes and brought a decrease in the extent of the flood-prone areas. The surface of the latter varied from 35.84 % in 1942 to 5.44 % in 2003. From 2003, the increased urbanization of the area gradually reduced the area that used to be covered by the Niayes although flooded areas rose by 9.25% in 2014. At that time, the built-up area prevailed with 37.27% at the expense of bare areas, waters surfaces, and especially woodlands. The densification of the road network is the major driver of the fragmentation of the Niayes and the main entryway to their occupation.